2015
DOI: 10.1002/ep.12107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium dodecyl sulfate on wheat (TriticumAestivumL.) seedlings

Abstract: In order to evaluate the phytotoxicity of the anionic surfactant sodium dodecyl sulfate (SDS), the inhibition of wheat seed germination was investigated. The effects of SDS on antioxidant enzyme activities [catalase and gluthione reductase (GR)], protein, soluble sugar, and proline in wheat (Triticum aestivum L.) seedlings were investigated after 6 days of SDS stress. With the increase in the SDS concentration, the root length of the wheat seedlings were inhibited markedly, and the protein content of the shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
4
6
0
Order By: Relevance
“…It was also determined that the levels of reduction in growth exhibited a positive correlation with the increase in SDS dosage. As compatible with our results, Chang et al [19] reported that SDS reduced the growth of wheat. It is possible that the SDS-induced growth retardation is due to destructions on the synthesis reactions.…”
Section: Effects Of Sds Applications On Root and Coleoptile Growthsupporting
confidence: 94%
See 4 more Smart Citations
“…It was also determined that the levels of reduction in growth exhibited a positive correlation with the increase in SDS dosage. As compatible with our results, Chang et al [19] reported that SDS reduced the growth of wheat. It is possible that the SDS-induced growth retardation is due to destructions on the synthesis reactions.…”
Section: Effects Of Sds Applications On Root and Coleoptile Growthsupporting
confidence: 94%
“…Also, it was determined in vitro that SDS breaks down the peptide bonds in amino acids and therefore denatures the proteins [25]. Our results clearly pointed out that SDS led to the critical decline in soluble protein content, corroborating previous result recorded for wheat grown in the presence of SDS [19]. The possible cause of these declines could be the disruptions in the cellular metabolic events during transcription, translation and post-translation.…”
Section: Effects Of Sds Applications On Soluble Protein Content and Psupporting
confidence: 90%
See 3 more Smart Citations